Efficacy and Safety of Omalizumab for the Treatment of Severe or Poorly Controlled Allergic Diseases in Children: A Systematic Review and Meta-Analysis - Ling Liu; Pengxiang Zhou; Pengxiang Zhou; Zhenhuan Wang; Suodi Zhai; Suodi Zhai; Wei Zhou (Frontiers Media S.A., 2022)
ObjectiveTo evaluate the efficacy and safety of omalizumab in the treatment of severe or uncontrolled allergic diseases in children.MethodsWe conducted a systematic search of the PubMed, Embase, CENTRAL, and clinicaltrials.gov databases up to 23rd July 2021, with no language limitations. Randomised controlled trials (RCTs) comparing omalizumab with other treatments or placebo in children with severe or inadequately controlled allergic diseases were considered. The primary outcomes of interest were asthma exacerbation rate, allergic symptom score, desensitisation achievement for food allergy (FA), and incidence of serious adverse events (SAEs). The study selection and data extraction were conducted independently by two researchers. Quality assessments were conducted using the Cochrane risk-of-bias tool, and data were pooled using a random-effects model if I2 was 50% or greater in the Cochrane Review Manager.ResultsOverall, 10 RCTs [six on severe asthma, one on atopic dermatitis (AD), one on seasonal allergic rhinitis [SAR], and one on FA] consisting of 2,376 participants met the inclusion criteria. For severe asthma, omalizumab may reduce exacerbations at 12 weeks [risk ratio (RR), 0.52; 95% confidence interval (CI), 0.31-0.89], 24 weeks (RR, 0.69; 95% CI, 0.55-0.85; GRADE: moderate-quality evidence), and 52 weeks (RR, 0.62; 95% CI, 0.40-0.94; GRADE: moderate-quality evidence) and reduce the dose of inhalation corticosteroid compared with placebo. For severe AD, the association between omalizumab and allergic symptom improvement [i.e., SCORing Atopic Dermatitis or Paediatric Allergic Disease Quality of Life Questionnaire (PADQLQ)] was not confirmed. For severe SAR, omalizumab showed greater improvement in symptom load scores and saved rescue medication days. For FA, omalizumab demonstrated superiority in desensitisation compared with placebo. To date, no clinically significant drug-related SAEs have been reported.ConclusionFor severe or uncontrolled asthma, AD, SAR, and FA, omalizumab may be associated with improved allergic symptoms and safety in children. Future studies should focus on the benefits and pharmacoeconomic evaluation of omalizumab in multiple allergic diseases compared with other treatments.Systematic Review Registration[https://www.crd.york.ac.uk/PROSPERO], identifier [CRD42021271863].